Use Of Web Technologies In Creating Electronic Educational Resources (Eurasian Journal of Learning and Academic Teaching, 2025)
This article examines the classification of services based on web technologies. Such services include: infographic creators (Venngage, Canva, Pictochart, Infogram, Creately, Tagxedo, Cacoo), multimedia poster creators (DesignCap, Glogster, ThingLink, Adobe Express), graphic editors (Picsart, Krita, Flyvi, PicMonkey), slide show creators (Photopeach, Weebl), interactive knowledge map creators (MindMeister, Storybird). The most popular of them are such platforms as Kahoot, Canva, Calameo, MindMeister, PhotoPeach, which are aimed at helping to form the basic skills necessary for achieving success in the creation of e-learning resources, in which issues of their use as a tool for creating e-learning resources are discussed